The Signposts Of Inquiry: Dewey’s Logic and Kuhn’s Philosophy of Science - Mayoral, Juan Vicente (Analysis. Journal of Philosophical Research, 2022)
In this article, I review John Dewey’s Logic: The Theory of Inquiry in order to show some points of coincidence with the work of a later author: Thomas S. Kuhn. I support the view that despite the disparities that their works sometimes show—and the reservations that Kuhn himself had about Dewey’s work—there are interesting coincidental points that help to offer a common standpoint that goes against more traditional views on logic, inquiry and scientific methodology. I focus on three main aspects: the contextual and social nature of logic; the significance they both grant to problem-solving contexts; and their convergence on a developmental view of the progress of knowledge.